(untitled) (African Journal of Biomedical Research, 2024)
Obesity is associated with cardiovascular disease (CVD) risk and type 2 diabetes mellitus (T2DM). Apolipoprotein (APO) C3 C3238G and C1100T gene polymorphisms are risk factors for CVD but their relationship with obesity and T2DM in Black Africans has not been fully elucidated. Association of these gene polymorphisms with hypertension and dyslipidemia among obese type 2 diabetics in a Southwest Nigerian population was assessed.One hundred and thirty-eight (138) non-obese diabetics, 107 obese diabetics, 100 obese non-diabetics and 100 control subjects attending metabolic clinic in Osun State Nigeria were enrolled. Anthropometric parameters were measured. Fasting blood sugar (FBS), lipid profile and APOC3 protein were estimated using standard lab procedures. APOC3 gene polymorphisms were analyzed by polymerase chain reaction - restriction fragment length polymorphism. Data were analyzed and significant level set at p<0.05. APOC3238G G allele was associated with higher risk of hypertension (OR=2.39, 95%CI=1.03-5.53; p=0.042) in obese diabetics compared to other groups. Highest frequency for hypertension was observed among obese diabetics expressing CC than CG and GG genotypes. GG genotype was associated with dyslipidemia in obese diabetic subjects exhibiting APO C3 C3238G single nucleotide polymorphism (SNP). Homozygous CC genotype showed highest frequency (χ2: 25.515, p<0.05) than other genotypes and was associated with increased atherogenic indices among obese diabetic subjects expressing APO C3 C1100T SNP. APOC3 C1100T gene and polymorphic alleles of the G variant of APOC3 C3238G gene were associated with dyslipidemia and hypertension in obese T2DM individuals, thereby contributing to increased risk of CVD among the studied population